The Taste of Art : Cooking, Food, and Counterculture in Contemporary Practices - Bottinelli, Silvia; Bottinelli, Silvia; D'Ayala Valva, Margherita; D'Ayala Valva, Margherita (Food and foodways, 2017)
Taste of art : methodologies and critical approaches. Can cuisine be art? A philosophical (and heterodox) proposal / Nicola Perullo -- Time changes everything : futurist/modernist cooking / Carol Helstosky -- From stove to screen : food porn, professional chefs, and the construction of masculinity in films / Fabio Parasecoli -- Spoerri reads Rumohr : the spirit of culinary art revisited / Margherita d'Ayala Valva -- Food art : multisensoriality and experience. Food, decay, and disgust -- Paul McCarthy's Bossy Burger as contemporary still life / Anja Foerschner -- In & on : herbs, fish, and Janine Antoni's touch / Silvia Bottinelli -- Luciano Fabro : bitter sweets for Nadezhda Mandelstam / Sharon Hecker -- The kitchen : intersections between the private and public spheres. Feminist art : kitchen testimony / Jody B. Cutler -- Es geht um die Wurst : on Peter Fischli and David Weiss's Sausage photographs / Edward A. Vazquez -- Elzḃieta Jabłonska's kitchen interventions: food, art, and the maternal identity / Barbara Kutis -- Eating out : food art in the public sphere. Artists and friends : Daniel Spoerri's Eat Art Gallery / Cecilia Novero -- Express yourself : Al's Cafe ́in context / Rachel Federman -- Ways of eating : tradition, innovation, and the production of community in food-based art / Laurie Beth Clark and Michael Peterson -- Not for art's sake : ethics, ecology, and sustainability. Joseph Beuys : gastrosophical aesthetics / Harald Lemke -- Provisional objects : Alison Knowles's Bean rolls / Nicole L. Woods -- Cooking and eating across species : Natalie Jeremijenko's Cross(x)species adventure club / Lindsay Kelley.